2021
DOI: 10.3758/s13423-021-02024-6
|View full text |Cite
|
Sign up to set email alerts
|

Experts use base rates in real-world sequential decisions

Abstract: Human behavior is often assumed to be irrational, full of errors, and affected by cognitive biases. One of these biases is base-rate neglect, which happens when the base rates of a specific category are not considered when making decisions. We argue here that while naïve subjects demonstrate base-rate neglect in laboratory conditions, experts tested in the real world do use base rates. Our explanation is that lab studies use single questions, whereas, in the real world, most decisions are sequential in nature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, another alternative is that the tasks themselves have priors. The idea here is that laboratory tasks may inherit the priors that similar everyday tasks have (cf., Hayes, Navarro, Stephens, et al, 2019;Link & Raab, 2021;Tauber, Navarro, Perfors, & Steyvers, 2017). If this were the case, then subjects would weigh differentially any explicit base-rate information that we provide, modulating it by their task-specific priors, and thus replicating differences across tasks that Exps.…”
Section: Methodsmentioning
confidence: 95%
“…However, another alternative is that the tasks themselves have priors. The idea here is that laboratory tasks may inherit the priors that similar everyday tasks have (cf., Hayes, Navarro, Stephens, et al, 2019;Link & Raab, 2021;Tauber, Navarro, Perfors, & Steyvers, 2017). If this were the case, then subjects would weigh differentially any explicit base-rate information that we provide, modulating it by their task-specific priors, and thus replicating differences across tasks that Exps.…”
Section: Methodsmentioning
confidence: 95%
“…The belief in hot streaks can provide valid cues to decide who to give shots to, and this behavior is supported by the fallacious belief in dependency 41 . This is further validated in 42 , which analyzed the sequential choices made by expert athletes and found that they were sensitive to base rates and adapted their decision strategies accordingly. Additionally, defensive pressure and shot difficulty increase during hot streaks, so that defenders seem to behave according to the hot-hand belief and try to force hot players into more difficult shots 37 .…”
Section: Introductionmentioning
confidence: 88%
“…Understanding how volleyball players make decisions has increasingly been the focus of research in the last few years (e.g., Castro et al, 2022;Degrenne et al, 2023;Link & Raab, 2022;Lola & Tzetzis, 2021;Ramos et al, 2022;Suárez et al, 2020). This is because the game dynamic that emerges from the players' simultaneous interactions of cooperation and opposition requires they frequently make decisions as a sine qua non for successful performances.…”
Section: Introductionmentioning
confidence: 99%